Aspek Perlindungan Hukum Nasabah - Fitri Fitri; Nadia Salzabila; Ilham Ilham (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to analyze the legal protection of customers within the Islamic banking system in Indonesia, both normatively and practically. In Islamic economic principles, customer protection is not merely a legal obligation, but a moral and religious responsibility rooted in the values of maqāṣid al-sharī‘ah, particularly in ensuring justice (al-‘adl), trust (tsiqah), and protection of wealth (ḥifẓ al-māl). This research applies a qualitative-descriptive approach through literature review and normative juridical analysis of statutory regulations, DSN-MUI fatwas, and relevant Islamic legal doctrines. The findings indicate that although legal frameworks such as Law No. 21 of 2008, DSN-MUI fatwas, and OJK regulations offer a substantial basis for customer protection, implementation faces several challenges. These include information asymmetry between banks and customers, low Islamic financial literacy, insufficient monitoring of standard contracts, and limited access to Sharia-based dispute resolution mechanisms. Therefore, the study recommends reformulating contract structures, strengthening the role of the Sharia Supervisory Board (DPS), and enhancing public education regarding their rights as Islamic banking customers. Legal protection must be both formally legal and ethically grounded in Islamic justice.